Prediksi Harga Rumah di Kabupaten Karanganyar Menggunakan Metode Regresi Linear - Ashary Vermaysha; Nurmalitasari Nurmalitasari (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2023)
This research aims to apply linear regression method in predicting house prices in Karanganyar Regency, using land area, building area, number of bathrooms, number of bedrooms, and electricity capacity as independent variables. A dataset consisting of house prices and the independent data was used in the analysis. The research results show that the predicted house prices have a relatively low level of accuracy, with an error of 651614542,27. To improve the prediction accuracy, three steps are recommended. First, adding data variations from several real estate websites to expand the sample and covered house characteristics. Second, expanding the dataset by adding supporting variables such as dates, which provide information about market trends and fluctuations. Finally, exploring alternative prediction algorithms that are more supportive than linear regression. The conclusion of this research is that although linear regression can be used to predict house prices in Karanganyar Regency, the accuracy level still needs to be improved. Therefore, the proposed recommendations need to be implemented to improve the prediction model. Thus, it is expected that house price predictions in Karanganyar Regency will become more accurate and useful for use in the property market.